A Retrospective Clinical Survey of Vertebral Compression Fractures - Ji Hye Oh; Yun Kyu Lee; Jae Soo Kim; Hyun Jong Lee; Sung Chul Lim (MEDrang Inc., 2018)
Background The purpose of this study was to review whether Korean medicine treatment was effective to maintain the spinal stability and to relieve spinal symptom by reviewing medical records of 18 vertebral compression fracture patients. Methods The subjects were 18 thoracolumbar compression fracture patients who were taken more than two lateral view x-rays of fractured vertebra from Jan, 2010 to June, 2018. They were divided into two groups: the time admitted into Department of Acupuncture & Moxibustion Medicine, Pohang Korean Medical Hospital of Daegu Hanny University from onset (Research 1) and whether or not they have a past history of osteoporosis (Research 2). Then, they were follow-up observed and compared by compression ratio and numerical rating scale (NRS) and so on. Results The amount of weekly compression rate increase of 18 patients was 1.76% per week. According to the result of Research 1, the patients group (14 patients) who were admitted into the hospital within 1-2 weeks from getting injury was 1.88% per week whereas the patients group(4 patients) who were admitted into the hospital within 3-4 weeks from getting injury was 1.22% per week. By Research 2 result, the patients group (7 patients) who had been diagnosed as an osteoporosis patient was 2.19% per week, and those (11 patients) who had not was 1.49% per week. There was a statistical significance in the change of the amount of compression rate increase in the case of Research 1, but there was not in the case of Research 2. NRS was decreased without significant difference regardless of the time admitted into the hospital and whether or not the patients had the past history of osteoporosis. Conclusions Considering that there were more amount of compression rate increase at 1-4 weeks from onset, it is necessary to offer treatment more actively on early time from onset. Further research is needed into the increase of compression rate by the patients' having a past history of osteoporosis or not. Given that NRS decreased without significant difference, it is assumed that Korean medicine treatment has a meaningful effect on relieving subjective symptom of patients who are diagnosed as vertebral compression fractures.